EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NHT DENGAN PMR DAN TSTS DENGAN PMR DITINJAU DARI KEMANDIRIAN BELAJAR SISWA - Zaotul Wardi; Mardiyana Mardiyana; Gatut Iswahyudi (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objective of this research was to investigate the effect of the learning models on learning achievement in mathematics viewed from self regulated learning. The learning models compared were cooperative learning model of the NHT type by using realistic mathematics approach, TSTS type by using realistic mathematics approach and the conventional learning model. The type of the research was a quasi experimental research. The population was all of the students in grade VIII of State Junior Secondary Schools of district of Eastern Lombok in academic year 2013/2014. The size of the sample was 308 students consisted of 104 in experimental class 1, 104 in experimental class 2, and 100 in control class. The instruments used were mathematics achievement test on the topic of geometry and questionnaire of self regulated learning. The data was analyzed by using two way analysis of variance with unbalanced cells. The conclusions of the research were as follows. (1) The cooperative learning model of the NHT type with the realistic mathematics approach resulted in alearning achievement equally well as the cooperative learning model of the TSTS type with realistic mathematics approach. The cooperative learning model of the NHT type and the cooperative learning model of the TSTS type with realistic mathematics approach provided better learning achievement than the conventional learning, (2) The students with the high self regulated learning had a better learning achievement in mathematics than those with the moderate and low self regulated learning categories, and the students with the moderate self regulated learning had a better learning achievement in mathematics than those with the low self regulated learning, (3) There was an interaction among learning models and the catagories of self regulated learning on learning achievement in mathematics.Keywords: NHT, TSTS, realistic mathematics approach, self regulated learning.